If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + -8 = 3(t + 5) Reorder the terms: -8 + 2t = 3(t + 5) Reorder the terms: -8 + 2t = 3(5 + t) -8 + 2t = (5 * 3 + t * 3) -8 + 2t = (15 + 3t) Solving -8 + 2t = 15 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. -8 + 2t + -3t = 15 + 3t + -3t Combine like terms: 2t + -3t = -1t -8 + -1t = 15 + 3t + -3t Combine like terms: 3t + -3t = 0 -8 + -1t = 15 + 0 -8 + -1t = 15 Add '8' to each side of the equation. -8 + 8 + -1t = 15 + 8 Combine like terms: -8 + 8 = 0 0 + -1t = 15 + 8 -1t = 15 + 8 Combine like terms: 15 + 8 = 23 -1t = 23 Divide each side by '-1'. t = -23 Simplifying t = -23
| 6n^2-21n=0 | | 3x+2x=125 | | 4(x+8)+x=-9(4-x) | | 32+2y-8=9y-11-2y | | Y+5(4y+2)=10(y+1)+9y | | 10r^2-3r-7=0 | | x+24+2x=-2-2x-9 | | 10r^2-57r+35=0 | | x+9=-5x+17 | | -16x-20=-14x+40 | | y^2+2.25=-3y | | 9x^2+42x+49= | | 3n+1=-25 | | 4x-(2x-4)=-2x+12 | | 8p+7-9p= | | 15p^2+20p-160=0 | | 18-5x=9+4x | | 9-18=36x | | 3x+2(2x+1)=-43 | | 4x-(2x-4)=-x+12 | | 7n^2+17n+6=0 | | 3(5k-6)=2(3k+4) | | 4(x+5)=5(x-8) | | 6x-2(x-8)=4(x+1)+9 | | 5b^2-43b-70=0 | | 20x+24+6x=3x-6+12 | | 7x+2-6x=10-22 | | b^2+6b-27=0 | | 1.6(5-x)=1.4(3-x) | | 4x^2+12x-6=0 | | 3x-14-2x=6 | | -4(2x+8)=-36 |